Lower rates of endoscopy and higher mortality in end‐stage renal disease patients with gastrointestinal bleeding: A propensity matched national study. Issue 3 (20th January 2022) - Garg, Rajat; Parikh, Malav P; Chadalvada, Pravallika; Singh, Amandeep; Sanaka, Krishna; Ahuja, Keerat R; Aggarwal, Manik; Veluvolu, Rajesh; Vignesh, Shivakumar; Rustagi, Tarun
Abstract: Background and Aim: Patients with end‐stage renal disease (ESRD) on hemodialysis are considered to be at higher risk of gastrointestinal bleeding (GIB) as compared with those without renal disease (NRD). We conducted a population‐based study using the National Inpatient Sample (NIS) database to study the outcomes of GIB in ESRD. Methods: Patients admitted with GIB (upper and lower) from 2005 to 2013 were extracted from the NIS database using ICD‐9 codes. Patients were divided into NRD and ESRD groups, and a 1:1 propensity matched analysis was performed. Various outcomes were compared in both groups, and subgroup analysis based on the timing of endoscopy was also performed. Results: A total of 218 032 patients were included in the study. There was an increase in inpatient admissions among ESRD patients with GIB with significant reduction in mortality ( P  < 0.001). In‐hospital mortality, length of stay, and total costs were significantly higher in ESRD patients as compared with NRD. ESRD patients were less likely to undergo endoscopic evaluation compared with NRD ( P  < 0.001). Late endoscopy (> 48 h) was associated with increased need for transfusion and health‐care utilization but without a significant difference in mortality as compared with early endoscopy. On multivariate analysis, endoscopy was associated with significantly lower rate of mortality in ESRD patients with GIB (odds ratio 0.28, P  < 0.0001). Conclusion: End‐stage renal disease patients with GIB had a significantly higher rate of mortality and a higher health‐care utilization with a lower rate of endoscopic evaluation. Endoscopy was associated with a lower mortality rate on multivariate analysis.